Electric vehicles and renewable energy for sustainable mobility: Insights from bibliometric, topic modeling, and societal impact analyses - Hira Tahir; Hasan Erteza Gelani; Sami El-Ferik; Muhammad Tayyab; Nima Khosravi (Energy Strategy Reviews)
As the global race to meet the Sustainable Development Goals intensifies, research on electric vehicles (EVs), renewable energy sources (RES), and sustainable mobility has grown significantly. This study provides a comprehensive overview of this evolving field using a novel multi-faceted methodological framework that integrates bibliometric analysis, machine learning-based topic modeling, and societal impact analysis. By combining these approaches, this work uniquely explores both research trends and societal implications. We analyzed 122 articles sourced from the Scopus database using Biblioshiny, the R package, and the Overton database to address four key research questions. Findings reveal growing research interest in EVs and RES, with Journal of Cleaner Production and Renewable and Sustainable Energy Reviews as the most impactful journals by citations and publication frequency. Keywords have evolved from technology-centric terms like “life cycle assessment” to broader societal concerns, including “sustainable mobility” and “carbon dioxide”. Six latent research topics were identified, with EV charging infrastructure and renewable energy integration being the most dominant. However, newer topics, such as sustainable EV adoption policies, are gaining traction. Societal impact analysis further reveals that research in this field significantly informs policy, demonstrating its relevance in driving societal change. However, contradictions between societal and research impacts suggest the need for a concurrent evaluation of both to assess real-world implications. This paper outlines theoretical, practical, and methodological implications, advocating for an integrated approach to assess research and societal impacts. Moreover, the proposed methodology guides future research, offering insights into the interplay between academic inquiry and real-world applications.